Treatment of chromium-contaminated soils using ladle furnace slag - George, Vivian (Nanyang Technological University, 2022)
Chromium (Cr) is a naturally occurring element found mostly within the Earth’s crust and exists in various oxidation states. Cr enters the environment mainly through anthropogenic sources namely industrial activities such as metal processing, tannery facilities and chrome pigment production. Cr can be easily leached into the soil through the means of water sources such as rivers. The presence of Cr in the environment poses adverse health impacts on mankind as heavy metals such as Cr are classified as carcinogens and are known to cause multiple organ damages. Ladle furnace slag (LFS) is a by-product of the steelmaking process. It is generated in the secondary refining process and is deemed as a waste product. As such the disposal of LFS into landfills is known to trigger environmental and economic issues. This research aims to use LFS as a binder in the solidification/stabilization (S/S) of Cr-contaminated soils. The Cr-contaminated soils were treated by conventional curing for 3 hours (h), 7 days, 28 days, and 56 days and carbonation curing for 2 h, 8 h, 32 h, and 152 h. Both the cured and carbonated Cr-contaminated soils were then subjected to pH tests, leaching tests, X-ray diffraction analysis (XRD), and field emission scanning electron microscope (FESEM) imaging with energy dispersive X-ray analysis (EDX). The results showed that conventional curing and carbonation curing were both effective in immobilizing Cr in LFS-stabilized Cr-contaminated soils. LFS-stabilized soils, with varying initial Cr concentrations, were found to contain lower concentrations of leached Cr when the conventional curing and carbonation time was increased. After conventional curing for 56 days and carbonation for 152 h, the leached Cr concentration were all below the limits of inert waste and three drinking water standards. The XRD and FESEM showed that ettringite was formed after curing, and carbonates were produced after carbonation.